2017
DOI: 10.1016/s0016-5085(17)30950-2
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Function Predicts Response to Anti-Integrin Biologic Therapy in Inflammatory Bowel Diseases

Abstract: The gut microbiome plays a central role in inflammatory bowel diseases (IBD) pathogenesis and propagation. To determine if the gut microbiome may predict responses to IBD therapy, we conducted a prospective study with Crohn's disease (CD) or ulcerative colitis (UC) patients initiating anti-integrin therapy (vedolizumab). Disease activity and stool metagenomes at baseline, and weeks 14, 30, and 54 after therapy initiation were assessed. Community α-diversity was significantly higher, and Roseburia inulinivorans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 37 publications
1
66
1
Order By: Relevance
“…Ananthakrishnan et al reported a decrease in abundance of five taxa associated with remission in response to anti-integrin biologic therapy -among them Bifidobacterium longum. 40 In contrast, we observed a large increase in abundance of two Bifidobacterium ASVs in antibiotic-associated remission samples.…”
Section: Discussioncontrasting
confidence: 58%
“…Ananthakrishnan et al reported a decrease in abundance of five taxa associated with remission in response to anti-integrin biologic therapy -among them Bifidobacterium longum. 40 In contrast, we observed a large increase in abundance of two Bifidobacterium ASVs in antibiotic-associated remission samples.…”
Section: Discussioncontrasting
confidence: 58%
“…With regard to vedolizumab, a broad number of observations has been made: While gene expression profiling identified a considerable number of genes that were significantly differentially expressed following vedolizumab therapy, none of them was able to predict treatment outcomes [28]. However, another study reported that response to vedolizumab was associated with pre-therapeutic composition of the intestinal microbiome [29]. Moreover, we had suggested that dynamic changes in the expression of α4β1 on peripheral blood CD4 + T cells in the early course of vedolizumab treatment and the baseline dynamic adhesion of CD4 + T cells to MAdCAM-1 in vitro might predict subsequent therapeutic response [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…92 Thus, changes in the trajectory of early microbiome after treatment may be a marker of a therapeutic response to inflammatory bowel disease (IBD). 93 Dysbiosis in patients with UC is summarized in Table 1. [66][67][68][69][70][71][72][74][75][76][77][78][79][80][81][82][83][84][85][86] Besides the effect of bacterial dysregulation, the influence of the interaction between human hosts and fungi, viruses and other microbes cannot be disregarded.…”
Section: Dysbiosis Of Intestinal Flora In Ucmentioning
confidence: 99%